Uji Sensitivitas Erythromycin dan Chloramphenicol Terhadap Salmonella sp. - Marti Silfia; Ida Fauziah; Sartini Sartini (Universitas Medan Area, 2022)
Salmonella sp. is a pathogenic microbe that causes digestive disorders that can cause death. One way to treat diseases caused by the bacteria Salmonella sp. is the use of antibiotic therapy. Salmonella sp. susceptible to antibiotic resistance due to improper use. The purpose of this study was to determine the susceptibility of Salmonella sp. Erythromycin and Chloramphenicol antibiotics. In this study, antibiotic sensitivity was tested using the Kirby-Bauer method (diffusion test) with a concentration of Erythromycin 250 mg/mL and antibiotics 500 mg/mL, Chloramphenicol antibiotics at concentrations of 250 mg/mL and 500 mg/mL. mL with 3 repetitions. The sample used in this study was a strain of Salmonella sp. suspended using Brain Heart Infusion Broth (BHIB) media and the antibiotic test was carried out using Mueller Hinton Agar (MHA) media. The greatest inhibition was seen in treatment with Chloramphenicol 500 mg/mL with an inhibition zone of 38.6 mm, followed by Chloramphenicol 250 mg/mL with an inhibition zone of 33.3 mm. The antibiotic Erythromycin 500 mg/ml had moderate inhibition against Salmonella sp. with an inhibition zone of 17.3 mm, while the antibiotic dose of Erythromycin 250 mg/ml produced a weak inhibitory effect on Salmonella sp. with a zone of inhibition of 12.5 mm.